DISTINCTIVE FEATURES OF CELLULOSE NANOCRYSTALLITES - Michael Yacob Ioelovich (Химия растительного сырья, 2024)
In this paper, a set of methods was used to study the structural characteristics and properties of cellulose nanocrystallites and free cellulose nanocrystalline particles (CNCs). It was shown that cellulose nanocrystallites have three main distinctive features. The first distinctive feature of cellulose nanocrystallites is their rod-like shape with a quite high aspect ratio and a low percolation threshold. The second distinctive feature of nanocrystallites is their highly developed specific surface area that leads to the spontaneous crystallization and aggregation of rod-like crystallites by their lateral planes. This aggregation process is thermodynamically favorable because it leads to a decrease in the specific surface area of nanocrystallites and a reduction of the thermodynamic potential. The third distinctive feature of cellulose nanocrystallites is the paracrystalline structure of their surface layers, which significantly affects structural characteristics such as lattice distortion, interplanar spacings, parameters, and volume of the crystalline unit cell, etc. Along with structure, the paracrystalline fraction affects also important physical and physical-chemical properties of cellulose, such as accessibility to deuteration, the content of CII-allomorph after cellulose alkalization, melting point of nanocrystallites, etc. Correlation equations were derived that provide to predict the structural characteristics and properties of nanocrystallites using the content of the paracrystalline fraction.